The Role of Topiramate in the Management of Cocaine Addiction: a Possible Therapeutic Option - Siniscalchi, Antonio; Bonci, Antonello; Biagio Mercuri, Nicola; Pirritano, Domenico; Squillace, Aida; De Sarro, Giovambattista; Gallelli, Luca (Current Neuropharmacology, 2015)
Topiramate (TPM) is an antiepileptic drug able to play a role in both neurological and psychiatric disorders. TPM facilitates gamma-aminobutyric acid (GABA) transmission and inhibits glutamatergic transmission (i.e. AMPA/kainate receptors). Several studies reported that the modulation of GABAergic and glutamatergic synaptic transmission may reduce cocaine reinforcement. Therefore, TPM could be used in the management of cocaine dependence.
Keywords: gamma-aminobutyric acid neurotransmission